2015
DOI: 10.1055/s-0035-1548741
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Extensive Soft-Tissue Defects with Concomitant Bone Defects in the Lower Extremity with the Latissimus Dorsi-Serratus Anterior-Rib Free Flap

Abstract: The LD-SA-rib flap provides a large soft-tissue component and a vascularized bone flap for reconstruction of composite large soft-tissue defects with concomitant bone defects of the lower extremity in a one-stage procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…An obvious drawback of choosing the rib for mandible reconstruction is that the rib bone is not solid as the fibular one: it cannot bear dental implants restricting the food intake to soft is that the vascularized rib may not be strong enough to bear the mechanical loads in the lower limb, because of the smaller crosssectional area of the rib. On the contrary, Sia et al 24 found that a single vascularized rib was sufficient to allow for eventual full weight bearing because of its ability to hypertrophy, thus increasing the cross-sectional area and cortical thickness of the bone. Therefore, indication for the flap in our case series is consistent with the literature reports.…”
Section: Discussionmentioning
confidence: 98%
“…An obvious drawback of choosing the rib for mandible reconstruction is that the rib bone is not solid as the fibular one: it cannot bear dental implants restricting the food intake to soft is that the vascularized rib may not be strong enough to bear the mechanical loads in the lower limb, because of the smaller crosssectional area of the rib. On the contrary, Sia et al 24 found that a single vascularized rib was sufficient to allow for eventual full weight bearing because of its ability to hypertrophy, thus increasing the cross-sectional area and cortical thickness of the bone. Therefore, indication for the flap in our case series is consistent with the literature reports.…”
Section: Discussionmentioning
confidence: 98%
“…In the flap transfer methods, the flap is taken towards conserving a part of the muscle. The proportion of branched samples should be clearer about arteries in that muscle (1,6). Serratus anterior muscle flaps have not been widely studied, particularly in Vietnam (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%